WEATHER AND TRAFFIC MONITORING SYSTEM IoT-Based TOWARDS JAMBI SMART CITY - Imti Tsalil Amri; Santoso Santoso; Teuku Djauhari; Brestina Gultom (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2021)
With the large number of vehicles on the road today, we often get stuck in a traffic jam on our way to a place. And the temperature or the weather that often changes sometimes also causes us to get stuck in a weather. Thus both these problems was made a journal WEATHER AND TRAFFIC MONITORING SYSTEM IoT-BASED TOWARDS JAMBI SMART CITY. This research uses descriptive research method. This method uses action techniques that focus on implementing actions with the aim of improving quality or solving problems in a group of objects and observing the success rate or impact of their actions.